Identifying the support needs of newly qualified professional nurses: A multiple stakeholder needs assessment - Yolandè Hayton; Yvonne Botma; Tanya Heyns (Elsevier, 2021)
When entering practice, newly qualified professional nurses may feel incompetent or be perceived as such. Newly qualified professional nurses may benefit from nurse residency programmes, guided by trained facilitators. Such programmes help to build competence, give nurses opportunities to learn and feel supported, prevent attrition, and develop nurses who are able to render quality care. Residency programmes that are developed using a person-centered approach have proven to be successful, and require multiple stakeholder involvement through collaboration, inclusion, and participation. Needs assessments are crucial in programme development. In this article we report on the support needs of newly qualified professional nurses during remunerated community service. The identified needs may be used to develop a Person-centered Nurse Residency Programme for the South African context.This qualitative study used an interpretive description approach. Data were collected from different stakeholders using multiple methods and was analysed during a consensus workshop. Stakeholder needs were categorised under four domains adopted and adapted from a recognised framework that directs person-centered practice. The four domains included learning outcomes of newly qualified professional nurses, prerequisites of the facilitator, learning environment and learning processes. The underlying themes in the domains indicated overlapping elements that influence the development of competencies across the different categories. Basic needs and competencies were identified as essential to the development of extended competencies.